2011
DOI: 10.1055/s-0031-1272471
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Hydrolaparoscopy

Abstract: Transvaginal hydrolaparoscopy (THL) is a modification of culdoscopy that can be used to evaluate the posterior uterus, pelvic sidewalls, and adnexae. Diagnostic THL can be done in the office under local anesthesia. Combined with diagnostic hysteroscopy and chromotubation, it can replace hysterosalpingography (HSG) as the first-line diagnostic test for the infertile woman. Studies have shown high patient tolerability with less pain reported postprocedure than with HSG. THL has been shown to have a high concorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…HSG has been a routine examination in many infertility centers as it is less costly and less invasive than laparoscopy. However, laparoscopy is superior in detecting peritoneal adhesions and endometriosis as compared with HSG [2,7,8]. In the present study, THLF was used for evaluating tubo-ovarian pathology in infertile women.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…HSG has been a routine examination in many infertility centers as it is less costly and less invasive than laparoscopy. However, laparoscopy is superior in detecting peritoneal adhesions and endometriosis as compared with HSG [2,7,8]. In the present study, THLF was used for evaluating tubo-ovarian pathology in infertile women.…”
Section: Discussionmentioning
confidence: 91%
“…Several reviews have validated the concept of THL in comparison to the gold standard: laparoscopy [10]. In a literature review of 187 patients from six studies including one prospective double-blind trial, a high concordance was found between THL and laparoscopy ranging from 77.8% to 100% [7,8]. In a review of 1516 THL, the rate of failure was 5.4% and these were linked to retroverted uterus and the presence of adhesions [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations